Textures of light : vision and touch in Irigaray, Levinas, and Merleau-Ponty - Vasseleu, Cathryn, 1957- (Warwick studies in European philosophy., 1998)
Textures of Light opens up new debates within continental and feminist philosophy. It will also be essential reading for anyone interested in visual studies and the philosophical issues of vision.